Perspective on Micro-Supercapacitors - Sun, Xiangfei; Chen, Kunfeng; Liang, Feng; Zhi, Chunyi; Xue, Dongfeng (Frontiers in Chemistry, 2022)
The rapid development of portable, wearable, and implantable electronic devices greatly stimulated the urgent demand for modern society for multifunctional and miniaturized electrochemical energy storage devices and their integrated microsystems. Micro-supercapacitors (MSCs) with high power density, fast charge/discharge rate, and ultra-long cycle life have attracted much attention in recent years. This article reviews material design and manufacturing technology in different MSCs along with devices integrate to achieve the targets of their various applications in recent years. Finally, We also critically prospect the future development directions and challenges of MSCs.